Optimizing the Performance of Unit PPA Polres Demak in Crime Settlement of Violence Against Children - Akbar, Muhammad Faiz (Advances in Police Science Research Journal, 2024)
A nation is developed if it has quality human resources in productive age. To achieve this, education is needed since early childhood because children are the future of the nation. But in fact, children who are supposed to be protected by the state are often the target of violence. To respond to this, the PPA Unit of Demak Police has an obligation to provide child protection. The problem formulated in this final project is to find out how the performance of the Demak Police PPA Unit in solving criminal acts of mobbing or child abuse. The theories and concepts that the author uses as an analysis knife are the theory of organization resources and elements, the theory of management functions, and the concept of optimization. The type of writing used is field research with data collection techniques using interviews, observations, and document studies. The analysis techniques that the author uses are data reduction, data presentation, and drawing conclusions. In this final project, it was found that the resolution of the crime of mobbing or child abuse was still not optimal. It is necessary to optimize the performance of investigators to achieve the expected conditions.